2011
DOI: 10.14705/rpnet.2011.9781908416001
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Teaching and Learning with Technology: Views of Emergent Researchers

Abstract: • Attribution: You must attribute the work in the manner specified by the publisher.• Noncommercial: You may not use this work for commercial purposes.• No Derivative Works: You may not alter, transform, or build upon this work.Research-publishing.net has no responsibility for the persistence or accuracy of URLs for external or third-party Internet websites referred to in this publication, and does not guarantee that any content on such websites is, or will remain, accurate or appropriate. Moreover, research-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 156 publications
(120 reference statements)
1
3
0
Order By: Relevance
“…In addition, the result for a One-sample t-test showed that there was a computably significant difference in the mean score between these mean scores and 4.0 (p<0.05). It pointed out the perceptions of Google Translate those multiple languages translation, ease of use, and save time are at a rather high level, thus, these results were suitable with the findings of Septiadi [1], Maulidiyah [38], Thouësny and Bradley [45], Krisnawati [50], Chandra and Yuyun [51], and Tsai [61]. Besides, Question 20 (M = 4.12, SD= 1.098), and Question 24 (M = 4.03, SD= 0.983) had slightly higher results than the others.…”
Section: Results From the Questionnairesupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the result for a One-sample t-test showed that there was a computably significant difference in the mean score between these mean scores and 4.0 (p<0.05). It pointed out the perceptions of Google Translate those multiple languages translation, ease of use, and save time are at a rather high level, thus, these results were suitable with the findings of Septiadi [1], Maulidiyah [38], Thouësny and Bradley [45], Krisnawati [50], Chandra and Yuyun [51], and Tsai [61]. Besides, Question 20 (M = 4.12, SD= 1.098), and Question 24 (M = 4.03, SD= 0.983) had slightly higher results than the others.…”
Section: Results From the Questionnairesupporting
confidence: 78%
“…Teachers might use audio or video chats to provide learning materials to their students and collect feedback, making it more efficient for both teachers and students. Thouësny and Bradley [45] said MALL helps learners enhance language abilities, has no time constraints (may be practiced at any time), and motivates learners, especially it improves students' learning behaviors, provides a good opportunity for EFL learners to practice the English language both inside and outside the classroom, and boosts students' language skills [9][46] [63].…”
Section: 5mentioning
confidence: 99%
“…Prior work shows that some migrants utilize mobile technologies to support their unmet language needs [10,32,33]. However, studies of migrants' use of mobile and other technologies is limited because understanding of mobile language learning tools has focused predominantly on foreign language learners at the post-secondary level [26,46] rather than those who must communicate in a non-native language to survive.…”
Section: Immigrants' Use Of Mobile Technologymentioning
confidence: 99%
“…However, studies of migrants' use of mobile and other technologies is limited because understanding of mobile language learning tools has focused predominantly on foreign language learners at the post-secondary level [26,46] rather than those who must communicate in a non-native language to survive. Literature in the Mobile-assisted Language Learning (MALL) space identifies the need for authentic synchronous communication [10,27,32]. A variety of mobile translation services and dictionaries have aimed to address the communication Scenario Prompt Speaking with people I need to speak to someone who speaks another language than I do.…”
Section: Immigrants' Use Of Mobile Technologymentioning
confidence: 99%